In vitro sensitivity of malignant melanoma cells lines to photon and heavy ion radiation - Aninditha, Kynann; Weber, Klaus-Josef; Brons, Stephan; Debus, Jürgen; Hauswald, Henrik (Clinical and translational radiation oncology, 2019)
Background - The role of radiotherapy in malignant melanoma is still in discussion due to its relative resistance to radiation. In various literature, heavy ions show a higher relative biological effectiveness than photons. The aim of this work is to evaluate the radiotherapeutical effect from photons as well as heavy ions on malignant melanoma cells and to indicate the possible radiosensitivity based on its proliferation-inhibitory effect. - Methods - Two different cell lines of malignant melanoma, WM115 (primary tumor) and WM266-4 (metastatic site, skin) were used in this in vitro study. The cells were treated with photons or heavy ions (C12 and O16 ions). Cell-proliferation assay using hemocytometer was used for the quantitative and qualitative evaluation of cell growth. Furthermore, flow cytometry was also used to analyze the cell cycle distribution. - Results - Heavy ions compared to photons and between the two heavy ion modalities, O16 ions showed an improved suppression of cell growth in both cell lines. Furthermore, a G2/M arrest was detected in both cell lines after all radiotherapy modalities - with the arrest increasing with the dose applied. - Conclusion - Heavy ions showed a greater inhibitory effect on cell proliferation compared to photons and an increased G2/M arrest. Therefore, C12 and O16 heavy ions might overcome the relative radioresistance of malignant melanoma to photons. Further research is warranted.
Gesehen am 02.04.2020